Preserving cultural identity: The imperative of prioritizing Indonesian character values in English textbooks to safeguard against cultural hegemony in language learning - Sudartini, Siti (Jurnal Pendidikan Karakter, 2024)
This article discusses the need to prioritize Indonesian cultural character values in English textbooks as a strategy to maintain cultural identity and counter the hegemony of Western cultural values in language learning in Indonesia. In the context of this research, the phenomenon is based on English textbooks for high school students in grades XI and XII in Indonesia. This research method uses library research. The main instrument of this research is the researcher himself as a "human instrument." The data analysis technique is descriptive qualitative, including data collection, display and discussion, and conclusion drawing. The results of the study show the following. Firstly, this study notes several trends that may be troubling, including the lack of representation of local values and the dominance of Western elements. Secondly, the factors causing this slide to involve both external and internal aspects. Externally, relating to the theory that language learning is inseparable from cultural learning provides a foundation for internalizing Western culture in English language learning. Internally, the influence of modernism and the syndrome of being a former Western colony led to an inferiority complex in cultural awareness, reinforcing the adoption of Western cultural values as the inevitable ideal standard. By exploring concrete strategies to promote Indonesian cultural values, this article advocates for a profound change in English teaching approaches to build a sense of identity and cultural diversity amidst the challenges of global values hegemony.